1970
DOI: 10.1139/m70-045
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of sporeforming bacteria associated with insects. I. Glucose catabolism in vegetative cells

Abstract: The catabolic pathways for use of glucose in proliferating vegetative cells of Bacillus thuringiensis, B. alvei, B. lentimorbus, and B. popilliae were studied by radiorespirometry. These organisms dissimilate glucose predominately via the Embden–Meyerhof–Parnas pathway and to a lesser extent by the pentose phosphate pathway. Extent of participation of concurrent pathways varied with each organism. Tentative evidence suggests that B. popilliae and B. lentimorbus, grown in a yeast extract – glucose medium, lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

1971
1971
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
2
9
1
Order By: Relevance
“…The phospholipid compositions of the Bangladeshi strains of B. cereus in this study were similar to those reported for other bacilli (Bulla et al, 1970). The predominant phospholipids of the genus Bacillus are PE, PG and DPG, accounting for over 90 % of the total phospholipid, while the minor components are the alanine ester of PG and lysophosphatidylethanolamine (Lang & Lundgren, 1970).…”
Section: Discussionsupporting
confidence: 83%
“…The phospholipid compositions of the Bangladeshi strains of B. cereus in this study were similar to those reported for other bacilli (Bulla et al, 1970). The predominant phospholipids of the genus Bacillus are PE, PG and DPG, accounting for over 90 % of the total phospholipid, while the minor components are the alanine ester of PG and lysophosphatidylethanolamine (Lang & Lundgren, 1970).…”
Section: Discussionsupporting
confidence: 83%
“…For example, the particular batch of yeast extract used in the medium had a pronounced effect. These factors may account for the difference between these results and those of Bulla et al (4). The FIG.…”
Section: 6contrasting
confidence: 56%
“…Bacillus thuringiensis, an economically important control agent for insect pests, catabolizes glucose primarily through the Embden-Myerhoff pathway while a small percentage is utilized for biosynthesis through the pentose phosphate shunt (Bulla et al 1970(Bulla et al , 1971Nickerson et a!. 1974).…”
mentioning
confidence: 99%